Perancangan Rest Area Tipe A Pada Tol Bocimi Jawa Barat dengan Langgam Arsitektur Neo Vernakular - Andriyana, Heri (Jurnal Arsitektur Wastu Padma, 2024)
The design of the type a rest area on the bogor-cianjur-sukabumi toll road aims to provide rest and recreation facilities for toll road users as well as space for business people to develop their businesses.  It is hoped that the existence of a transportation node, apart from accommodating its main function, can become a space to introduce the potential of the local area.  The design refers to the neo-vernacular architectural approach, which is a conceptual approach in architectural design that places the local values of the local community combined with a technological approach to accommodate new functions. The discussion method is divided into several stages, including research on space requirements and environmental potential. The results of the discussion resulted in the idea that the neo vernacular concept was applied to building mass layout, choosing roof shapes and sundanese architectural forms.